Digital Mammography A Holistic Approach - Hogg, Peter; Kelly, Judith; Mercer, Claire; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This up-to-date, evidence-based book covers the whole range of mammography and mammography-related techniques used in practice, and also the rapid and increasingly sophisticated evolution of mammographic clinical practice and technology.   A wide range of topics, from the psychological and emotional support required from the practitioner to all aspects of screening and symptomatic mammographic imaging, are discussed.   Digital Mammography: A Holistic Approach is aimed at radiographers, technicians, technologists, physicists, nurses and medical practitioners worldwide, and enables the reader to gain a better understanding of techniques, equipment and anatomy.  .
Part 1. Introduction and background -- 1. Anatomy and physiology: Breast anatomy -- 2. Breast Density and Influencing Factors -- 3. Aetiology and epidemiology of breast cancer -- 4. Other breast diseases -- 5. Signs and symptoms of breast cancer with management pathways -- 6. Disease progression – local and distal spread (mechanisms) -- 7. Mammography Screening:  Philosophy – evidence for and against -- 8. Screening programs for breast cancer in Europe -- Part 2. Caring for Patients and Clients -- 9. Sue’s story: the big journey -- 10. Psychological considerations in attending for mammography screening -- 11. Emotional Intelligence -- 12. Client-practitioner interactions within breast care services -- 13. The use of Digital Health Technology and Social Media to support Breast Screening -- 14. Pain in mammography -- 15. Tissue viability and skin tearing in mammography -- Part 3. Equipment -- 16. Mammography imaging equipment -- 17. Equipment quality control -- 18. Radiation dose in mammography -- 19. Mammographic Density -- Part 4. Imaging Techniques -- 20. Recording clinical and client information prior to imaging -- 21. Practical mammography -- 22. Mammography Compression: A Need for Mechanical Standardization -- 23. Repetitive Strain Injury -- 24. Supplementary Mammographic Projections -- 25. Magnification and compression views -- 26. Specimen Imaging -- 27. Imaging the Augmented Breast -- 28. Imaging Bariatric, Post Surgical and Limited Mobility Clients -- 29. Male Mammography -- 30. Digital Breast Tomosynthesis -- 31. Reflection on the Oslo Tomosynthesis Screening Trial -- 32. Purpose of Interventional Procedures -- 33. Image Guided Interventional Techniques -- 34. Contrast enhanced investigations -- Part 5. Service Quality Assurance -- 35. Radiographic Service Quality.-36. Observer studies in Mammography.
Keywords: Radiology; Oncology .; Imaging / Radiology; Diagnostic Radiology; Oncology